Análisis bibliométrico de las narrativas transmedia en la era de la convergencia de medios (2012-2022) - Vásquez Romero, Carlos Augusto (2024)
Transmedia narratives represent a novel form of communication and information in the era of media convergence. These narratives allow a story to spread across multiple platforms, encouraging active audience participation. The purpose of this paper is to analyze the scientific production on transmedia narratives in the media published between 2012 and 2022 in the field of social sciences. For the analysis we applied a bibliometric analysis with quantity and quality indicators. For the evaluation we searched the Scopus databases for the terms “transmedia storytelling” and “media” (in spanish and english). One hundred twenty-eight were found that met the criteria proposed for the research. The results show an existing knowledge gap, but also an evolution in the topics investigated and how this narrative is manifested in digital media, beyond fiction. In this way, the transmedia narratives are a trend in constant transformation that promises an interesting future in communication and entertainment.